PHONOLOGICAL AWARENESS IN PRESCHOOL CHILDREN WITH DEVELOPMENTAL LANGUAGE DISORDER - Jovanovska, Mira; Lazarovska, Vesna; Zelić, Mirna (Medicinski časopis, 2025)
ABSTRACTObjectives. To determine the level of development of phonological awareness in children with developmental language disorder at the age of four to six years compared to children with typical language development.Methods. Ninety children aged 4 to 6, of both genders, divided into three groups, participated in the study. The Phonological Awareness Test was applied. The study was conducted during January and February 2024.Results. The analysis of the results showed that phonological awareness deficit was not more frequently manifested in children with developmental language disorder compared to children of typical development, as well as that there was no statistically significant difference in the manifestation of phonological awareness deficit in children with developmental language disorder in relation to gender, in terms that these problems are more frequently found in boys.Key words: developmental language disorder, phonological awareness, typical language development